STANDARD COST EFFECT ON PERFORMANCE OF SELECTED LISTED FOOD AND BEVERAGE COMPANIES IN NIGERIA, WEST AFRICA - OLUWAYEMISI, Ali-Momoh Betty; AYODEJI, Adisa Lateef; OLUFEMI, Ibifunmilola David; OLUWASEUN, Deji-Oyeleye Bosede; KEHINDE, Agbede Gabriel (Annals of Spiru Haret University. Economic Series, 2022)
The aim of this research was to determine whether or not a change in standard cost will improve the financial standing of a sample of Nigerian food and beverage manufacturers. This goal was reached by analyzing the relationship between the price of raw materials, the price of labor, and the price of manufacturing overhead on the bottom line of Nigerian food and beverage firms. Five manufacturing firms were chosen at random for the research. Nestle Plc, Cadbury Nig Plc, P.Z. Cussons Nig. Plc, and Presco Nig. Plc are the food and beverage companies that were included in the survey. In this case, we used secondary data that we had gathered over the previous decade (2010-2020). Panel estimation methods (pooled OLS, fixed effect estimation, and random effect) and a post estimation test were used to examine the compiled data. The results showed that a firm’s performance in the manufacturing sector in Nigeria was significantly correlated with its manufacturing overhead costs, but negatively correlated with its raw material costs, and positively correlated with its labor costs. The research indicated that careful consideration of raw material costs and the maintenance of effective standard costing across all labor costs were necessary to obtain the desired results. Because of the significant savings in time and money that may be achieved via the use of standard costing principles and procedures, the research concludes that all food and beverage businesses in Nigeria should do so.